In vivo Anti-Cancer Effects of Resveratrol Mediated by NK Cell Activation - Yoojin Lee; Heewook Shin; Jongsun Kim (Karger Publishers, 2020)
Natural killer (NK) cells are innate immune lymphocytes that play an important role in anti-viral and anti-tumour immune responses. Several cancer immunotherapy approaches targeting NK cells are currently in clinical or preclinical development. Here, we aimed to find food nutrients that activate NK cells and determine their usefulness as candidates for anti-cancer and anti-metastatic drugs. Resveratrol appeared to activate NK cells most effectively among the substances tested and synergistically increased IFN-γ secretion and NK cell cytotoxicity with interleukin-2 (IL-2). CD107a, NKp30, and NKG2D expression levels were upregulated on the surface of NK cells upon treatment with resveratrol in combination with IL-2 compared with treatment with IL-2 alone. Moreover, NK cell activity in human and mouse whole blood was enhanced upon treatment with resveratrol. Most importantly, administration of resveratrol effectively inhibited tumour growth and metastasis in mice. In conclusion, we suggest that resveratrol may represent a candidate anti-cancer drug that acts by activating NK cells in vivo.